Experimental and theoretical studies of the molecular structure of 7-Methyl-3-[(3-methyl-3-mesityl-cyclobutyl]-5-phenyl-5H-thiazolo [3,2-?]pyrimidine-6-carboxylic acid ethyl ester - Acar, Betul; Yilmaz, Ibrahim; Caliskan, Nezihe; Cukurovali, Alaaddin (Elsevier, 2017)
In this work, the title molecule, 7-Methyl-3-[(3-methyl-3-mesityl-cyclobuty1]-5-phenyl-5H-thiazolo[3,2 alpha]pyrimidine-6-carboxylic acid ethyl ester (C30H34N2O2S1), was synthesized and characterized by FT-IR spectroscopy and single crystal X-ray diffraction. The compound crystallizes in the triclinic space group P2(1)/c. with Z = 4, a = 14.1988(6), b = 19.0893(5), c = 10.1325(4) angstrom, V = 2674.56(17) A(3). The optimized structure parameters of the studied molecule was determined theoretically using HF/6-31G(d) and B3LYP/6-31G(d) methods for ground state, and compared with previously reported experimental findings. The calculated harmonic vibrational frequencies are scaled and they are compared with experimental frequencies obtained by FT-IR spectra. The electronic properties, such as HOMO and LUMO energies, and molecular electrostatic potential (MEP) are also performed. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: X-ray; DFT and HF calculation; B3LYP; IR spectrum